2022
DOI: 10.2147/jir.s381036
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to High-Density Lipoprotein Ratio is Associated with Hemorrhagic Transformation in Patients with Acute Ischemic Stroke

Abstract: Background: Hemorrhagic transformation (HT) is one of the most common and severe complications in patients with acute ischemic stroke (AIS). It indicates a poor prognosis in AIS patients. However, the association of neutrophil to high-density lipoprotein ratio (NHR) with HT remains unclear. Purpose: This study examined whether the NHR has a predictive effect on HT in AIS patients and explored the predictive cutoff value of the NHR. Methods: This is a retrospective study and consecutively included AIS patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Given that in ammatory cells play an important role in the development of IS, researchers have begun to explore ways to improve the prognosis of stroke patients by targeting in ammatory cells to alleviate brain tissue damage. By constructing a mouse model of tethered middle cerebral artery, Hu et al found that suppressing the number of neutrophils in the ischaemic region of acute ischaemic stroke minimised cell death and promoted functional recovery of the nervous system [22] ; Huang et al found that microglial IL-1RA ameliorates brain injury after ischaemic stroke by inhibiting astrocytic CXCL1-mediated neutrophil recruitment [23] ; and AlRuwaili et al demonstrated that inhibition of phosphodiesterase 5 (PDE5) promotes neurological recovery in AIS patients by modulating the brain cyclic adenosine monophosphate (cAMP)/cyclic guanosine monophosphate (cGMP)/nitric oxide (NO) pathways [24] . Currently, studies on reducing the severity of AIS and promoting neurological recovery by alleviating neuroin ammation have been carried out in mouse models, and there is an urgent need for additional researchers to increase their efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Given that in ammatory cells play an important role in the development of IS, researchers have begun to explore ways to improve the prognosis of stroke patients by targeting in ammatory cells to alleviate brain tissue damage. By constructing a mouse model of tethered middle cerebral artery, Hu et al found that suppressing the number of neutrophils in the ischaemic region of acute ischaemic stroke minimised cell death and promoted functional recovery of the nervous system [22] ; Huang et al found that microglial IL-1RA ameliorates brain injury after ischaemic stroke by inhibiting astrocytic CXCL1-mediated neutrophil recruitment [23] ; and AlRuwaili et al demonstrated that inhibition of phosphodiesterase 5 (PDE5) promotes neurological recovery in AIS patients by modulating the brain cyclic adenosine monophosphate (cAMP)/cyclic guanosine monophosphate (cGMP)/nitric oxide (NO) pathways [24] . Currently, studies on reducing the severity of AIS and promoting neurological recovery by alleviating neuroin ammation have been carried out in mouse models, and there is an urgent need for additional researchers to increase their efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found a linear positive correlation between NHR and the risk of developing non-MAP. NHR is a conventional, inexpensive, and readily available blood indicator and serves as an effective, independent indicator of the severity of various diseases [ 16–18 , 25 ]. Higher NHR values were independently associated with a higher risk of haemorrhagic transformation in patients with acute ischaemic stroke [ 16 ] and with cardiovascular risk in healthy individuals [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Haematologic inflammation indicators, such as white blood cell (WBC) count, C-reactive protein, neutrophil–lymphocyte ratio, platelet–lymphocyte ratio, and systemic inflammatory response index, are independently associated with the severity of ABP [ 12–15 ]. Additionally, the neutrophil to high-density lipoprotein cholesterol ratio (NHR) is associated with the severity of various diseases, including acute ischaemic stroke, cardiovascular disease, and Parkinson’s disease [ 16–18 ]. However, no studies have investigated the association between NHR and ABP severity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 , 27 ] In fact, Wei et al reported that NLR might have a greater negative diagnostic value in predicting stroke-associated pneumonia in patients with AIS. [ 28 ] Meanwhile, Zhang et al [ 29 ] found NHR to be a reliable and simple independent predictor of hemorrhagic transformation in patients with AIS. Chen et al [ 16 ] further revealed that high NHR levels are associated with poor prognosis 3 months after intravenous thrombolysis in patients with AIS.…”
Section: Discussionmentioning
confidence: 99%